2016
DOI: 10.1007/s10924-016-0864-6
|View full text |Cite
|
Sign up to set email alerts
|

Polyester Composites Reinforced with Corona-Treated Fibers from Pine, Eucalyptus and Sugarcane Bagasse

Abstract: This study aims to evaluate plant fibers that were surface activated with NaOH and corona discharge before incorporating in ortho unsaturated polyester-based fiber composites. It demonstrates the potential use of lignocellulosic particles, especially eucalyptus that presented the higher values for all the mechanical properties analyzed. The corona discharge treatment increased impact strength and tensile strength of the composites, and decreased water absorption. SEM images showed that the surface activation g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The anatomical characteristics did not differ for all characteristics ( Table 2). The values of the fiber cell length and diameter are in agreement with the literature, and the SCB has intermediate values between Eucalyptus and Pine wood (Hemmasi et al, 2011;Mesquita et al, 2017). Hemmasi et al (2011) measured just fibers and found similar mean values: 1590 µm (length), 20.96 µm (cell diameter), 5,64 µm (wall thickness) and 9.72 µm (lumen width).The cell wall fraction is related to the rigidity of the cell and values above 60% are normally related to stiffer fibers (Guimarães Junior et al, 2010).…”
Section: Pith and Fiber Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…The anatomical characteristics did not differ for all characteristics ( Table 2). The values of the fiber cell length and diameter are in agreement with the literature, and the SCB has intermediate values between Eucalyptus and Pine wood (Hemmasi et al, 2011;Mesquita et al, 2017). Hemmasi et al (2011) measured just fibers and found similar mean values: 1590 µm (length), 20.96 µm (cell diameter), 5,64 µm (wall thickness) and 9.72 µm (lumen width).The cell wall fraction is related to the rigidity of the cell and values above 60% are normally related to stiffer fibers (Guimarães Junior et al, 2010).…”
Section: Pith and Fiber Characteristicssupporting
confidence: 88%
“…Due the chemical composition and the mechanical processing, SCB has some drawbacks such as: high water absorption (WA) (Lee and Mariatti, 2008;Xu et al, 2009); high amounts of ash and extractives that can affect the adhesive cure and the adherence between particles and adhesive (Widyorini et al, 2005;Xu et al, 2009); and, fibers (cells) with less stiffness and more damaged because of the sugarcane milling process (Guimarães Júnior et al, 2012;Mesquita et al, 2017). New studies have been done trying to overcome those problems.…”
Section: Introductionmentioning
confidence: 99%
“…Long and narrow fibers are preferable because they confer higher mechanical properties to the composites (Guimarães Jr et al, 2010). Mauve fibers have higher length and lower width compare to others natural fibers, also tested in polyester composites, such as pine, Eucalyptus and sugarcane bagasse (Mesquita et al, 2017).…”
Section: Properties and Characterization Of The Compositesmentioning
confidence: 99%
“…Mauve fibers have higher WF (69.4%) compare to others natural fibers, also tested in polyester composites, such as pine (26.7%), Eucalyptus (55.9%) and sugarcane bagasse (47.3%) (Mesquita et al, 2017).…”
Section: Fiber Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation